1996
DOI: 10.1099/00222615-44-4-311
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro proteinase production by oral Candida albicans isolates from individuals with and without HIV infection and its attenuation by antimycotic agents

Abstract: In-vitro proteinase production by oral Candida afbicans isolates from patients with and without HIV infection (18 isolates from each group) was assessed by image analysis of a plate assay, with bovine serum albumin (BSA) as a substrate. The effect of subminimal inhibitory concentrations (sub-MICs) of nystatin, amphotericin B, clotrimazole and miconazole on in-vitro proteinase production by these yeast isolates was also investigated. Proteinase production by C. albicans isolates from patients with HIV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
2
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 0 publications
6
48
2
5
Order By: Relevance
“…Similar to the results of Ollert et al (1995) and Wu et al (1996), we found increased expression of proteinase activity in isolates from HIV-infected individuals compared with HIV-uninfected subjects. The proteinases of C. albicans require a low pH for optimal activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the results of Ollert et al (1995) and Wu et al (1996), we found increased expression of proteinase activity in isolates from HIV-infected individuals compared with HIV-uninfected subjects. The proteinases of C. albicans require a low pH for optimal activity.…”
Section: Discussionsupporting
confidence: 92%
“…The proteinases of C. albicans require a low pH for optimal activity. Interestingly, xerostomia, changes in salivary composition and the lower pH found in HIV-infected individuals favour the activity of proteinases (Wu et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Candida is also well-known to produce enzymes, such as secretory aspartyl proteinases (Saps), which facilitate both attachment to and penetration of the mucous membranes (Samaranayake and MacFarlane, 1990). Interestingly, subminimal inhibitory concentrations (sub-MIC) of amphotericin B are capable of curtailing the activity of this enzyme in oral C. albicans isolates (Wu et al, 1996), thus reducing its pathogenicity. On the contrary, exposure of C. albicans to sub-MIC of amphotericin B has resulted in enhanced resistance to apo-lactoferrin-mediated candidal cell death (Nikawa et al, 1994).…”
Section: (F) Median Rhomboid Glossitismentioning
confidence: 99%
“…The proteolytic activity of oral C. albicans isolates in vitro is also curtailed by nystatin (Wu et al, 1996). However, similar to amphotericin B, exposure of C. albicans to sub-MIC of nystatin has resulted in an increased resistance to apo-lactoferrin-mediated cell death (Nikawa et al, 1994).…”
Section: (F) Median Rhomboid Glossitismentioning
confidence: 99%
See 1 more Smart Citation